2002
DOI: 10.1177/0892705702015002449
|View full text |Cite
|
Sign up to set email alerts
|

Mechanics of Damage and Degradation in Random Short Glass Fiber Reinforced Composites

Abstract: The present study is part of an ongoing research work on damage of random short fiber reinforced composites. First, the tensile behavior of the material was studied. In its initial state, the material is planarly isotropic elastic. As the load increases, damage induces an anisotropic degradation of the material properties. Then, the degradation mechanisms were studied from microscopic observations of polished specimens. Finally, a theoretical model based on damage mechanics is proposed to predict the mechanica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 7 publications
(11 reference statements)
0
6
0
Order By: Relevance
“…Given that each strand contains about 300 fibers, the length-to-diameter ratio of a strand is 175. Microscopic observations of the composite [7] still revealed the presence of a significant number of entrapped air bubbles, and confirmed the random orientation of the fibers through the thickness. Therefore, the material was expected to initially exhibit an in-plane isotropic behavior.…”
Section: Materials Descriptionmentioning
confidence: 57%
See 2 more Smart Citations
“…Given that each strand contains about 300 fibers, the length-to-diameter ratio of a strand is 175. Microscopic observations of the composite [7] still revealed the presence of a significant number of entrapped air bubbles, and confirmed the random orientation of the fibers through the thickness. Therefore, the material was expected to initially exhibit an in-plane isotropic behavior.…”
Section: Materials Descriptionmentioning
confidence: 57%
“…As can be observed, as the applied stress increases, elastic modulus progressively decreases while the permanent strains increase. From the elastic modulus, variable D 1 could be evaluated using Equation (7). Poisson's ratios are also indicated in Table 1.…”
Section: Experimental Characterization Of Damage In Compositesmentioning
confidence: 99%
See 1 more Smart Citation
“…4), consistent with other studies [7,8], have demonstrated that fiber alignment affects the mechanical properties of SCFR-PEEK. Model parameters were 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 9 identified based on the experimental results of compressive tests, using the methodology reported for PEEK polymers [21] and assuming brittle linear elastic behavior in compression [34][35][36].…”
Section: Modelling Behavior Of Peek Compositementioning
confidence: 99%
“…Equation (47) must be obtained experimentally and in previous work [7,11] it has been shown that, using uniaxial tensile loading data, an initially isotropic short fibre composite can be described with a linear relationship:…”
Section: Determination Of Damage Parameters For the Current Stress Statementioning
confidence: 99%